Green and eco-friendly approaches for the extraction of chitin and chitosan: A review - Mohan, Kannan; Ganesan, Abirami Ramu; Ezhilarasi, P.N.; Kondamareddy, Kiran Kumar; Rajan, Durairaj Karthick; Sathishkumar, Palanivel; Rajarajeswaran, Jayakumar; Conterno, Lorenza (Carbohydrate polymers, 2022)
Chitin is one of the most diverse and naturally occurring biopolymers, and it is mainly present in crustaceans, insects, and fungi. Chitosan is derived from chitin by deacetylation process. It is important to note that the conventional chemical method of extracting chitin includes disadvantages and it poses various environmental issues. Recently, the green extraction techniques have perceived substantial development in the field of polymer chemistry. A variety of methods have been successfully developed using green extraction techniques for extracting chitin and chitosan from various resources. It includes the use of ionic liquids (ILs), deep eutectic solvents (DES), microbial fermentation, enzyme-assisted extraction (EAE), microwave-assisted extraction (MAE), ultrasonic-assisted extraction (UAE), subcritical water extraction (SWE), and electrochemical extraction (ECE). In this review, the extraction of chitin and chitosan using greener approaches were summarized. In addition, challenges, opportunities and future perspectives of green extraction methods have also been narrated. [Display omitted]